2012
DOI: 10.7763/ijiee.2012.v2.202
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Integrated Marketing CommunicationTools for Different Stages of Customer Relationship inDigital Era

Abstract: The purpose of this paper is to study the objectives, tools and media appropriate for each customer relationship stage and present a model showing this. Information era and changes caused by that have had an undeniable impact on these concepts. Thus, impacts of digital era and internet on dimensions of the presented model are discussed. Customer relationship management programs are focused on acquiring best customer, maintaining and encouraging him to consume products and services of the company more. The succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Communication (IMC) Ekhlassi et al (2012) study the suitable media for each customer relationship stage (customer acquisition, retention, and development) and found that communication was the key success to every relationship. They used Duncan and Ouwersloot (2008) concept of customer acquisition, in which new companies and products should focus their marketing efforts, that is gained by IMC and advertising, on customer acquisitions, in order to build awareness.…”
Section: Relationship Marketing and Integrated Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication (IMC) Ekhlassi et al (2012) study the suitable media for each customer relationship stage (customer acquisition, retention, and development) and found that communication was the key success to every relationship. They used Duncan and Ouwersloot (2008) concept of customer acquisition, in which new companies and products should focus their marketing efforts, that is gained by IMC and advertising, on customer acquisitions, in order to build awareness.…”
Section: Relationship Marketing and Integrated Marketingmentioning
confidence: 99%
“…On the other hand, Ekhlassi et al (2012) used Swift (2001) definition of CRM as an "organizational approach to understanding and influencing on customer behavior through a meaningful relationship in order to improve customer acquisition, retention, loyalty and profitability processes." They reveal that CRM divided into three main stages, which have the same concept of the customer relationship life cycle stages mentioned above, as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Communication tools will cover a wide range of different tools for delivering planned messages to target audiences through various media in order to build a brand. As an approach to ensuring that brand personality, messages, and position are derived from a unique strategy and are delivered to the customer with synergy among all communication elements, communication can be defined as follows: Ekhlassi, Maghsoodi and Mehrmane [16]. The concept of a research model will be developed on the basis of various studies that have been conducted in order to make the research process more efficient.…”
Section: Communication Toolsmentioning
confidence: 99%
“…On the other hand, Ekhlassi et al (2012) posited that the cost-effectiveness of digital marketing communication tool has made it more relevant in the buyer-seller relationship because it could be used to replace the traditional customer relationship channels by focusing on the major goal of customer relationship which is the acquisition of best customers, maintaining and encouraging them to consume the product and services through marketing communication functions such as; advertising, sales promotion, direct marketing, etc. (Ekhlassi et al, 2012).…”
Section: Conceptual Analysismentioning
confidence: 99%